Revision der paläarktischen Arten von Phytosciara Frey (Diptera: Sciaridae). - Mohrig, Werner; Menzel, Frank (Contributions to Entomology = Beiträge zur Entomologie, 1994)
The 28 Palaearctic species of Phytosciara are considered to be a monophyletic, belonging to the subgenera Phytosciara s. str. (4 species), Dolichosciara (11 species) and Prosciara (12 species). Phytosciara breviantennata (Mohrig & Mamaev) was unplaced until now. Five species (Ph. nepalensis spec. nov., Ph. oldenbergi spec. nov., Ph. subflavipes spec. nov., Ph. subornata spec. nov., Ph. subungulata spec. nov.) are described as new and 10 new combinations and 1 new synonyms are given. Keys to species and their habitats and distribution are discussed Phytosciara coheri spec. nov., from Thailand is described and the types of Sciara nigra Wiedemann and Psilomegalosphys xanthogaster Enderlein are revised. Nomenclatural Acts magnifica (Mohrig & Menzel, 1994) (Bradysia), nom. n.; comb. n. pro Phytosciara (Phytosciara) melanura Mohrig & Krivosheina, 1983, nec Mohrig & Mamaev, 1982 neofusca (Mohrig & Krivosheina, 1982) (Bradysia), comb. n. hitherto Phytosciara neofusca zingiberis (Sasakawa, 1985) (Bradysia), comb. n. hitherto Phytosciara zingiberis nodulosa (Mohrig & Krivosheina, 1985) (Lycoriella (Hemineurina)), comb. n. hitherto Phytosciara (Phytosciara) nodulosa breviantennata (Mohrig & Mamaev, 1983) (Phytosciara), comb. n. hitherto Corynoptera breviantennata flavipes (Meigen, 1804) (Phytosciara (Dolichosciara)), Lectotype described as Sciara flavipes nepalensis Mohrig & Menzel, 1994 (Phytosciara (Dolichosciara)), spec. n. subflavipes Mohrig & Menzel, 1994 (Phytosciara (Dolichosciara)), spec. n. subornata Mohrig & Menzel, 1994 (Phytosciara (Dolichosciara)), spec. n. halterata (Lengersdorf, 1926) (Phytosciara (Phytosciara)), Lectotype described as Sciara halterata macrotricha (Lengersdorf, 1926) (Phytosciara (Phytosciara)), Lectotype described as Psilomegalosphys macrotricha oldenbergi Mohrig & Menzel, 1994 (Phytosciara (Phytosciara)), spec. n. coheri Mohrig & Menzel, 1994 (Phytosciara (Prosciara)), spec. n. filichaeta (Hippa & Vilkamaa, 1991) (Phytosciara (Prosciara)), comb. n. described as Prosciara filichaeta lobata Antonova, 1977 (Phytosciara (Prosciara)), syn. n. of Phytosciara (Prosciara) ussuriensis Antonova, 1977 pectinifera (Hippa & Vilkamaa, 1991) (Phytosciara (Prosciara)), comb. n. described as Prosciara pectinifera pentacanta (Hippa & Vilkamaa, 1991) (Phytosciara (Prosciara)), comb. n. described as Prosciara pentacanta plusiochaeta Hippa & Vilkamaa, 1991 (Phytosciara (Prosciara)), comb. n. hitherto Prosciara plusiochaeta porrecta (Lengersdorf, 1929) (Phytosciara (Prosciara)), Lectotype described as Sciara (Neosciara) porrecta prosciaroides (Tuomikoski, 1960) (Phytosciara (Prosciara)), comb. n. described as Bradysia prosciaroides subungulata Mohrig & Menzel, 1994 (Phytosciara (Prosciara)), spec. n. ungulata (Winnertz, 1867) (Phytosciara (Prosciara)), Lectotype described as Sciara ungulata xanthogaster Enderlein, 1911 (Psilomegalosphys), Lectotype Phorodonta Coquillet, 1910 (Sciaridae), nom. n. for Odontonyx Rübsaamen, 1894, nec Stephens, 1828